Q-Switched Neodymium-Doped Yttrium Aluminum Garnet Laser Therapy for Pigmented Skin Lesions: Efficacy and Safety - Karn, D; KC, S; Amatya, A; Razouria, EA; Timalsina, M; Suwal, A (Kathmandu University Medical Journal, 2013)
Background Nepalese population with Fitzpatrick skin types III-V has high prevalence of pigmentary disorders and it is a growing cosmetic concern. Q-Switched Neodymium- Doped Yttrium Aluminum Garnet (QS Nd-YAG) laser is an efficacious tool in the treatment of pigment disorders. Objective To highlight the efficacy and safety profile of various pigment disorders. Methods A prospective study done in Dhulikhel Hospital, Kathmandu University Hospital from January 2009 to January 2011. Patients undergoing laser for pigmented skin lesions were followed for response and safety profile. We included total 270 patients in the study with various disorders especially nevus, tattoos and melasma. Settings were repeated at 3-4 weeks interval and response was evaluated on clinical basis. Efficacy was then evaluated according to various parameters. Results For nevus, total 840 treatment sessions had been performed with an average of 6.88 sessions (range 3-11). Nd: YAG laser was very efficacious in removal of blue and black colored tattoos with an average of 7.9 and 9.5 sessions respectively. However, red mixed with blue and or green tattoos were relatively resistant to treatment and required average 10.33 treatment sessions. Melasma and freckles both responded to the therapy but recurrence rate was high. Conclusion Our results indicate that QS Nd: YAG laser is an effective modality for pigment disorders among Nepalese population. Nevus and melasma respond well but recurrence rate of melasma is high. Blue tattoos respond well while mixed colored tattoos are quite resistant to Nd: YAG laser alone. Transient pain and temporary hyperpigmentation are common side effects. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 46-50 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7343